2019
DOI: 10.1617/s11527-019-1364-7
|View full text |Cite|
|
Sign up to set email alerts
|

A new short-term aging model for asphalt binders based on rheological activation energy

Abstract: Short-term aging of asphalt binders is an inevitable phenomenon during mix production and laydown that significantly affects the rheological properties of asphalt binders and further contributes to the deterioration of pavement performance. This paper presents a new short-term aging model for asphalt binders. The new model focuses on the binder viscosity as the target property and incorporates the rheological activation energy for the model development. It consists of four model coefficients and two essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The AE, which acts as a boundary to viscous flow, must be achieved before flow can occur [45]. Equation (4), sometimes described as the "Arrhenius" formula, can be applied to predict the temperature-viscosity relationship with asphalt cements [46].…”
Section: Activation Energy Of Flow (Ae) Methodsmentioning
confidence: 99%
“…The AE, which acts as a boundary to viscous flow, must be achieved before flow can occur [45]. Equation (4), sometimes described as the "Arrhenius" formula, can be applied to predict the temperature-viscosity relationship with asphalt cements [46].…”
Section: Activation Energy Of Flow (Ae) Methodsmentioning
confidence: 99%
“…Te total strain is the sum of all the above three strains. Te MSCR test data of PG 64-10 bitumen at 0.1 kPa creep stress was used to determine Burger's model parameters using equation (5). Te ftted parameters are shown in Table 4.…”
Section: Efect Of Wco Addition Of Creep-recovery Behaviormentioning
confidence: 99%
“…Figure 1 shows the typical variation in the viscosity of the bitumen in the mixture. It can be seen that the rate of change of viscosity during the short-term ageing is signifcantly higher compared to long-term ageing as a thin flm of bitumen is exposed to high temperature for at least 2-4 hours [5].…”
Section: Introductionmentioning
confidence: 99%
“…One-day-aged asphalt concrete was found to show better fatigue performance than unaged asphalt concrete, and asphalt concrete aged over 1-day showed deteriorated fatigue performance. Zang et al [17] suggested a new short-term aging model for binders that focused on the viscosity and rheological activation energy, and was calculated from the conventional properties such as penetration, kinematic viscosity, AV, and viscosity-temperature susceptibility (VTS) values of unaged asphalt binders. According to this aging model, the rheological activation energy of asphalt was increased linearly proportional to SA, and provided accurate viscosity predictions in both lab and field short-term aging.…”
Section: Aq Modelingmentioning
confidence: 99%